Dampak Food Vlogger terhadap Minat Beli Konsumen di Kalangan Mahasiswa Bandung Raya, Indonesia - Dewi Anggraeni (International Journal Administration, Business & Organization, 2022)
The aim of this research is to conduct an analysis of the factors that play a role in influencing students' buying interest in the Greater Bandung area, Indonesia. In its implementation, this research involved a total of 100 respondents as research samples. The method used is a quantitative descriptive approach, and the data collected is then analyzed using statistical techniques such as regression, correlation and descriptive approaches. The results of this research explicitly show that the impact of the presence of food vloggers has a significant simultaneous influence on students' buying interest of 47.2%. Regression, correlation and descriptive analyzes help describe and understand the complex relationships between the variables involved in the context of student buying interest. Therefore, it can be concluded that the existence of food vloggers as a whole plays an important role in shaping the preferences and purchasing decisions of students in the Greater Bandung area.